2011
DOI: 10.1007/s11751-010-0099-3
|View full text |Cite
|
Sign up to set email alerts
|

Arthroplasty versus internal fixation for femoral neck fractures in the elderly

Abstract: We studied 140 patients with femoral neck fractures treated from January 1999 to December 2006. There were 68 men and 72 women with a mean age of 72 years (range 60–80 years). Seventy patients were treated with closed reduction and internal fixation (group A), and 70 patients with hip arthroplasty (group B). The duration of surgery, length of hospitalization, complications, postoperative Harris hip score, and need for reoperation were recorded. Group B had significantly higher blood loss, increased surgical ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…In general, less invasive surgical techniques are preferred for frail, elderly patients [24][25][26]. This is reflected in our data in which hemiarthroplasties were 20% more common and total hip replacements were 125% more common in the low RCRI cohort, which were younger, less burdened by comorbidities, and more fit for surgery, based on their CCI and ASA scores respectively.…”
Section: Discussionmentioning
confidence: 82%
“…In general, less invasive surgical techniques are preferred for frail, elderly patients [24][25][26]. This is reflected in our data in which hemiarthroplasties were 20% more common and total hip replacements were 125% more common in the low RCRI cohort, which were younger, less burdened by comorbidities, and more fit for surgery, based on their CCI and ASA scores respectively.…”
Section: Discussionmentioning
confidence: 82%
“…A recent comparative study showed that functional outcomes were higher in the arthroplasty group in the first year following the operation but the results became comparable from the second year onward. 36 Another common argument is that osteoporosis in the physiologically older group affords poor purchase of internal fixation devices and increases the failure rates. 37 However, in 1 study that objectively examined this claim, no correlation was found between bone mineral density and the clinical outcome of the fracture.…”
Section: Fracture Of the Neck Of Femur In Adultsmentioning
confidence: 99%
“…On the other hand, it has been controversial for aged patient. The failure rate of osteosynthesis is reported to be as high as 20 % in elderly femoral neck fracture due to osteonecrosis, nonunion and fixation failure, and also post-operative ambulation might be delayed in this population due to the difficulty of achieving firm fixation [ 3 , 4 ]. Especially, the elderly asian women have low bone density compared to the westerners, which may be a risk factor that can lead to osteoporotic fractures and show the higher possibility of fixation failure after femoral neck fracture [ 5 ].…”
Section: Introductionmentioning
confidence: 99%